Evaluation of the Effects of Artemisia herba-alba on Intestinal Parasite Infections in Domestic Pigeons (Columba livia) in Albeida City, Libya - Saad, Kaula A.; Alsanousi, Somia A.; Alkailani, Hanan A. (Scientific Journal of University of Benghazi, 2021)
The first aim of the current study is to investigate the presence of intestinal parasitic infections in domestic pigeons (Columba livia) in Albeida City, Libya. individually faces samples from 100 birds were collected and examined using direct smearing and the flotation method. The majority of the pigeons (60%) were likely to have mixed infections with one or two of intestinal parasites (Eimeria 40%, Capillaria 50%, Heterakis 8% and Raillietina 2%). The second goal is to determine the anti-parasites effects of Artemisia herba-alba aqueous extract on intestinal parasite infection. The birds were divided into 5 groups of ten each for different concentration of Artemisia herba-alba extracts (5 %, 10 %, 15 % 20 % and control group) administered orally once a day for 3 days. The results showed that there was no significant reduction in the numbers of internal parasites (Eimeria oocysts and helminths eggs) in infected pigeons.